Edge effect as source of heterogeneity of the tree component in an araucaria forest in southern Brazil Efeito de borda como fonte da heterogeneidade do componente arbóreo em uma floresta com araucárias no sul do Brasil - Pscheidt F.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.This study aimed to evaluate changes in the organization of tree species communities due to edge effects in a forest remnant in southern Brazil. Five transects were installed in the study area, perpendicular to the forest edge, with the dimensions of 100×20 m, subdivided into ten plots. The edge sector was defined for the distance of 0-50 m and the interior for the distance of 50-100 m. All trees with circumference at breast height ≥ 15.7 were measured, identified and classified into regeneration guilds. The sectors were compared using the t test for normally distributed variables, Mann-Whitney test for non-normal distributions, rarefaction, for richness, and Chi-square test applied to a contingency table, to check the distribution of individuals of different regeneration guilds. The sectorization as a function of edge and interior represented an important source of forest heterogeneity, once the most marginal part of the fragment was characterized by a tree component of higher density, smaller average height and prevalence of individuals of light demanding species. In the context of biodiversity conservation of the Araucaria Forest, this study suggests the need for conservation of forest fragments which size and spatial configuration allow the existence of interior area, in order to contemplate the protection of non-tolerant species of edge conditions.